Resection of Clival Chordoma Through the Anterior Clivectomy: 2-Dimensional Operative Video - Paulo A. S. Kadri; Kenan I. Arnautović; Walid Ibn Essayed; Ossama Al‐Mefty (2021)
Clival chordomas are rare malignant behaving tumors that grow, locally invade, metastasize, and seed, and they have a high recurrence rate.1,2 The longest disease control is achieved by radical resection followed by high doses of radiation therapy, commonly proton beam.3 To achieve radical tumor removal, multiple surgical procedures through different approaches might be required.4 Since the chordoma's origin is, and remains, extradural, an extradural approach is preferred, and can lead to intradural extension. Anterior approach is frequently utilized to remove the midline-located tumor and the eroded clivus.5 Several midline approaches were utilized, including the transbasal, transfacial, transcervical, open door, and Lefort's maxillotomies1; however, the same tumor removal can be achieved with a simple extension of the trans-sphenoidal approach, by resecting the anterior maxillary wall, of the contralateral to the lesion preponderant side.5 This approach coupled with the use of neuronavigation on mobile head and endoscopic-assisted technique allowed to achieve a wide and direct exposure, with the ability to resect extra- and intradural tumors.2,5 Lately, the endonasal endoscopic technique became popular as an alternative4; however, we found a great advantage in the ability to combine the stereoscopic microsurgical technique with the endoscopic dissection, in addition to avoiding the extensive nasal dissection and its complications. We present a case of a 63-yr old woman with an upper clivus chordoma compressing the brainstem who underwent a gross total resection by endoscopic-assisted microscopic techniques through an anterior clivectomy approach. Patient consented to the procedure and publication of her images.